Potential utility of melatonin as an antioxidant therapy in the management of sickle cell anemia - Silva, Danilo Grünig Humberto da [UNESP]; Ricci Júnior, Octávio; Almeida, Eduardo Alves de [UNESP]; Bonini-Domingos, Claudia Regina [UNESP] (Wiley, 2014)
This study aimed to assess antioxidant eﬀects of melatonintreatment compared to N-acetylcysteine (NAC) and to their combination in asickle cell suspension. Sickle erythrocytes were suspended in phosphate-buﬀered saline, pH 7.4, composing external control group. They were alsosuspended and incubated at 37°C either in the absence (experimental controlgroup) or in the presence of NAC, melatonin and their combination atconcentrations of 100 pM, 100 nM and 100 lM for 1 hr (treatment groups).The melatonin inﬂuences were evaluated by spectrophotometric [hemolysisdegree, catalase (CAT), glutathione S-transferase (GST), glutathioneperoxidase (GPx), glutathione reductase (GR), glucose-6-phosphatedehydrogenase (G6PDH), and superoxide dismutase (SOD) activities] andchromatographic methods [glutathione (GSH) and malondialdehyde (MDA)levels]. Incubation period was able to cause a rise about 64% on hemolysisdegree as well as practically doubled the lipid peroxidation levels (P < 0.01).However, almost all antioxidants tested treatments neutralized this incubationeﬀect observed in MDA levels. Among the antioxidant biomarkers evaluated,we observed a modulating eﬀect of combined treatment on GPx and SODactivities (P < 0.01), which showed ~25% decrease in their activities. Inaddition, we found an antioxidant dose-dependent eﬀect for melatonin onlipid peroxidation (r = 0.29; P = 0.03) and for combined antioxidanttreatments also on MDA levels (r = 0.37; P = 0.01) and on SOD activity(r = 0.54; P < 0.01). Hence, these ﬁndings contribute with important insightthat melatonin individually or in combination with NAC may be useful forsickle cell anemia management.
Keywords: alternative therapy; antioxidant capacity; hemoglobin S; melatonin; oxidative stress